Seedling emergence and vigour improvement by priming muskmelon (Cucumis melo) seeds under diverse environments - Singh, Rajinder; Singh, Didar (The Indian Journal of Agricultural Sciences, 2020)
Priming is known to improve the germination of seed even under stress conditions. The present investigation was conducted at vegetable Research Farm, PAU, Ludhiana during 2016-17. Seeds of Punjab Sunehri variety of muskmelon (Cucumis melo L.) were treated with eleven priming treatments (hydration, GA3, KNO3, KH2PO4 and ethrel along with placing in wet gunny bags for 24 h and 48 h and hydration + FYM for 48 hours) along with control were sown in two diverse environments. Seeds sown during third week of February shows better germination and vigour than January sown seeds. Seed priming treatments were significantly better over the control. Treating the seed with potassium dihydrogen orthophosphate for 12 hr and then placing in wet gunny bags for 48 hr resulted in maximum germination (%), speed of germination, seedling length, dry weight and vigour indices in January sown seeds and par with GA3 and at ethrel treatments in February sown seeds.